Colorimetric sensor based on bubble wrap and camera phone for glucose determination - Martínková, Pavla; Pohanka, Miroslav (Journal of Applied Biomedicine, 2016)
Glucose is a typical marker of diabetes mellitus but it corresponds also with metabolic syndrome, immune disorders and some types of poisoning. Hence fast, low cost and simple method for its determination is required. Bubble wrap, cheap and available material, was used for immobilization of glucose oxidase (GOx) and peroxidase (POx), the enzymes necessary for colorimetric determination of glucose. Method is based on reaction of enzymes (immobilized in sol-gel membrane inside the bubbles) with substrates glucose and o-phenylenediamine dihydrochloride (o-PD) providing intensive coloration. The color change can be easily tracked by phone integrated camera. Color intensity expressed in red-green-blue (RGB) color model was used for displaying of photos and for gaining numeric data representing concentrations of glucose. The assay exerted good correlation of color intensity with the concentration of glucose, adequately low limit of detection (750 mmol/l) for glucose blood assay, no influence of interferents or matrix substances and by sufficient long term stability of sol-gel membrane. The sensor was found as low-cost simple way to analyze glucose blood levels with promising prospects in the field of portable devices.
Keywords: Gels; Membranes, Artificial; indikátory a reagencie; membrány umělé; Colorimetry; Biosensing Techniques; krevní glukóza; peroxidasa; fotografování; Photography; Reagent Kits, Diagnostic; plastické hmoty; gely; reagenční diagnostické soupravy; biosenzitivní techniky; Indicators and Reagents; Peroxidase; Glucose Oxidase; Plastics; kolorimetrie; Blood Glucose; glukosaoxidasa